Anatomy of the cavernous muscles of the kangaroo penis highlights marsupial–placental dichotomy - Warburton, N.; Bateman, Bill; Fleming, P. (Wiley Blackwell Publishing Ltd, 2019)
The mammalian penis is a complex hydraulic organ of cavernous (spongy) tissue supported by both smooth and skeletal muscle structures. In placental mammals, the paired ?Musculus ischiocavernosi anchor the corpora cavernosa to the pelvis (at the ischium), and the paired M. bulbospongiosi converge as they envelop the base of the corpus spongiosum. Male marsupials have a dramatically different anatomy, however, in which both sets of paired muscles remain separate, have a bulbous, globular shape and do not have any direct connection to the pelvis. Here we provide the first detailed anatomical investigation of the muscles of the penis in the western grey kangaroo (Macropus fuliginosus) incorporating dissection, histology, vascular casting and computed tomography. The M. ischiocavernosus and M. bulbospongiosus form massive, multipennate bodies of skeletal muscle surrounding the paired roots of the corpus cavernosum and corpus spongiosum, respectively. Bilateral vascular supply is via both the artery of the penis and the ventral perineal artery. Histological examination reveals cavernous tissues with substantial smooth muscle supported by fibroelastic trabeculae, surrounded by the thick collagenous tunica albuginea. The M. ischiocavernosus and M. bulbospongiosus are known to function during erection of the penis and ejaculation via muscular contraction increasing blood pressure within cavernous vascular tissues. The thick muscular anatomy of the kangaroo would be well suited to this function. The absence of any connection to the bony pelvis in marsupials suggests the possibility of different mechanisms of action of these muscles with regard to reduction of venous return, eversion from the cloaca, or movements such as penile flips, which have been described in some placental mammals. This highlights a greater diversity in form and function in the evolution of the mammalian penis than has been previously considered.